Risk and Return Analysis in Indonesian Banking Industries - Pandu Adi Cakranegara (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2021)
The bank, like any other business entity, is an entity established for profit. There are risks involved to increase profit. The higher the yield to be obtained, the consequence is more increased the risk is borne. However, the banking industry is different from other sectors because banks are an industry whose survival is based on trust. Banks need to maintain the level of risk to avoid disruptions to the failure of their business operations. This study focuses on linking the operational risks borne by banks and bank profitability. Operational risk is seen from short-term operational risk, long-term operational risk, operational risk related to the bank's upper line, operational risk related to its bottom line, and operational risk associated with business scale. The research method used is quantitative research methods using statistics. The statistical method chosen is multiple linear regression because there are several independent variables with a dependent variable. The outcome of the multiple linear regression shows that risk management has a significant positive relationship with profitability. These findings indicate that bank operational risk management is not a burden that reduces profitability but instead increases profitability by reducing risk.